Новый вид рода Andrena F. (Hymenoptera, Apoidea, Andrenidae) из Югославии - Осычнюк, А.3. (Вестник зоологии, 1975)
New species Andrena grozdanici sp. n. collected by Prof. S. S. Grozdanić in the Belgrade environs is described. The species differs from the similar in appearance species Andrena trimmerana Kby. (subgenus Hoplandrena) by interstitial nervulus. The female is also distinguished by a fine punctation of the clypeus, shape and sculpture of the labruni process, size of the orbital sulcus, a longer 2nd segment of the antenna flagellum and sparse thick hairs of the tibia bursa, the male-by a long 2nd segment of the antenna flagellum, mandibles without process or thorn and gonostyles broadened at the top. The holotype (19) is preserved at the collection of the Institute of Zoology of the Ukrainian Academy of Sciences (Kiev).